Classical algebra its nature, origins, and uses - Cooke, Roger (John Wiley & Sons, Inc., 2008)
Classical Algebra provides a complete and contemporary perspective on classical polynomial algebra through the exploration of how it was developed and how it exists today. Complemented with a mixture of historical remarks and analyses of polynomial equations throughout, this book is excellent for mathematics courses of the undergraduate level. It also serves as a valuable resource to anyone with a general interest in mathematics.